Cardiomyopathy as presenting sign of glycogenin‐1 deficiency—report of three cases and review of the literature. Issue 1 (7th October 2016) - Hedberg‐Oldfors, Carola; Glamuzina, Emma; Ruygrok, Peter; Anderson, Lisa J.; Elliott, Perry; Watkinson, Oliver; Occleshaw, Chris; Abernathy, Malcolm; Turner, Clinton; Kingston, Nicola; Murphy, Elaine; Oldfors, Anders
Abstract: We describe a new type of cardiomyopathy caused by a mutation in the glycogenin‐1 gene ( GYG1 ). Three unrelated male patients aged 34 to 52 years with cardiomyopathy and abnormal glycogen storage on endomyocardial biopsy were homozygous for the missense mutation p.Asp102His in GYG1 . The mutated glycogenin‐1 protein was expressed in cardiac tissue but had lost its ability to autoglucosylate as demonstrated by an in vitro assay and western blot analysis. It was therefore unable to form the primer for normal glycogen synthesis. Two of the patients showed similar patterns of heart dilatation, reduced ejection fraction and extensive late gadolinium enhancement on cardiac magnetic resonance imaging. These two patients were severely affected, necessitating cardiac transplantation. The cardiomyocyte storage material was characterized by large inclusions of periodic acid and Schiff positive material that was partly resistant to alpha‐amylase treatment consistent with polyglucosan. The storage material had, unlike normal glycogen, a partly fibrillar structure by electron microscopy. None of the patients showed signs or symptoms of muscle weakness but a skeletal muscle biopsy in one case revealed muscle fibres with abnormal glycogen storage. Glycogenin‐1 deficiency is known as a rare cause of skeletal muscle glycogen storage disease, usually without cardiomyopathy. We demonstrate that it may also be the cause of severe cardiomyopathy and cardiac failure without skeletal muscle weakness. GYG1 should be included in cardiomyopathy gene panels.